Gender‐dependent pharmacokinetics of olaparib in rats determined by ultra‐high performance liquid chromatography/electrospray ionization tandem mass spectrometry. (17th January 2020) - Su, Guosheng; Qin, Lihua; Su, Xiaoye; Tao, Chuanmin; Wei, Yesheng
Abstract: The aim of the present study was to develop a liquid chromatography/electrospray ionization tandem mass spectrometry (LC–ESI–MS/MS) method for the determination of olaparib in rat plasma. The plasma samples were processed using one‐step protein precipitation with acetonitrile and then separated on Waters Acquity BEH C18 column (50 × 2.1 mm, particle size 1.7 μm) using water containing 0.1% formic acid and acetonitrile as mobile phase with optimized gradient elution. Mass spectrometric detection was carried out by selective reaction monitoring mode via positive ESI mode with precursor‐to‐product transitions of m/z 435.3 > 367.1 and m/z 443.1 > 375.2 for olaparib and 2 H8 ‐olaparib (internal standard). The method was linear over the concentration range 0.1–2000 ng/ml with correlation coefficient >0.9987. The lower limit of quantitation was 0.1 ng/ml. The method showed excellent accuracy and precision, negligible matrix effect and high extraction recovery. The validated method was subsequently utilized to determine the concentration of olaparib in rat plasma and further applied to the pharmacokinetic study of olaparib in rat plasma. Our results demonstrated that olaparib showed gender‐dependent pharmacokinetics in rats. Compared with that in males, olaparib showed high plasma exposure, long half‐life, low clearance and high bioavailability in females.